2006
DOI: 10.1038/nrd2201
|View full text |Cite
|
Sign up to set email alerts
|

Drugs for bad bugs: confronting the challenges of antibacterial discovery

Abstract: The sequencing of the first complete bacterial genome in 1995 heralded a new era of hope for antibacterial drug discoverers, who now had the tools to search entire genomes for new antibacterial targets. Several companies, including GlaxoSmithKline, moved back into the antibacterials area and embraced a genomics-derived, target-based approach to screen for new classes of drugs with novel modes of action. Here, we share our experience of evaluating more than 300 genes and 70 high-throughput screening campaigns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
2,094
1
38

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,283 publications
(2,145 citation statements)
references
References 26 publications
12
2,094
1
38
Order By: Relevance
“…However, bacteria naturally develop resistance, and contributory factors include: the limited number of therapeutic targets that antimicrobials act on; the greater need due to the demands of modern medicine and aging populations; their misuse and overuse; most importantly, the failure to find new antimicrobials to restock the pipeline [2]. Hence, antimicrobial resistance now constitutes a serious global threat [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, bacteria naturally develop resistance, and contributory factors include: the limited number of therapeutic targets that antimicrobials act on; the greater need due to the demands of modern medicine and aging populations; their misuse and overuse; most importantly, the failure to find new antimicrobials to restock the pipeline [2]. Hence, antimicrobial resistance now constitutes a serious global threat [3].…”
Section: Introductionmentioning
confidence: 99%
“…The development of genetic methods that enabled testing of enzyme essentiality appeared to offer a short cut to ensure the value of particular targets. A seminal paper from investigators at GSK in 2007, however, reported that the systematic expression of scores of target proteins and their screening against libraries of hundreds of thousands of compounds yielded absolutely nothing in terms of new antimicrobials (Payne et al 2007). Other companies had been suffering similarly frustrating times and the academic laboratories involved in rather lower-level throughput screening could report the same.…”
Section: Introductionmentioning
confidence: 99%
“…Although most stakeholders agree that new antibiotics could tackle this unmet medical need, opinions vary on how new antibiotics could be discovered and brought into the market in a cost-effective manner. [1][2][3] Two considerations would probably meet with unanimous consensus: the golden era of antibiotic discovery is gone and it will not be repeated; and genomics, combinatorial chemistry and highthroughput screening do not represent the magic bullet to fill the pipeline with new developmental drug candidates. In this respect, it is important to underline the contribution that natural products, especially those of microbial origin, can provide to antibiotic discovery, as advocated by Demain 4,5 on several occasions.…”
mentioning
confidence: 99%